Pengaruh Pemahaman Etika terhadap Karakter Pemuda Kristen di Era Modern - Kasmir Gideon Situmeang; Beriman Simatupang; Hatopan Hulu; Diana Martiani Situmeang M.pd (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
His research explores how ethical understanding influences the character of Christian youth in the modern era. Through a qualitative approach, data was collected from in-depth interviews with Christian youth aged 18-25 years in various church communities. The research results show that understanding Christian ethics significantly influences young people's decision making, attitudes and daily behavior, even though they are faced with the challenges of modernization and globalization. This study emphasizes the importance of ethics education in strengthening character with integrity among Christian youth.